2009
DOI: 10.1097/mpg.0b013e318196df3e
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Treatment in Pediatric Crohn Disease Patients Intolerant or Resistant to Purine Analogues

Abstract: Methotrexate is beneficial in maintaining remission and steroid-sparing treatment in children with Crohn disease following failure of thiopurine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 17 publications
1
40
0
2
Order By: Relevance
“…From week 1 to 16, nausea and/or vomiting was reported in 34% of those in the methotrexate group, headache and nasopharyngeal symptoms were each reported in 23%, increased aminotransferase levels in 9%, and alopecia in 6%. A retrospective study of 25 patients aged <18 years with Crohn's disease who had previously failed purine analogues were subsequently treated with methotrexate (median dose 12.5 mg/m 2 ) along with folic acid found that nausea was the most common side effect, occurring in 9%; the next most common adverse event was persistently elevated transaminases in 6.2% . No infectious or hematological complications were reported over a mean treatment duration of 13.1 ± 8.7 months (range 0.5–36 months, median 12 months).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…From week 1 to 16, nausea and/or vomiting was reported in 34% of those in the methotrexate group, headache and nasopharyngeal symptoms were each reported in 23%, increased aminotransferase levels in 9%, and alopecia in 6%. A retrospective study of 25 patients aged <18 years with Crohn's disease who had previously failed purine analogues were subsequently treated with methotrexate (median dose 12.5 mg/m 2 ) along with folic acid found that nausea was the most common side effect, occurring in 9%; the next most common adverse event was persistently elevated transaminases in 6.2% . No infectious or hematological complications were reported over a mean treatment duration of 13.1 ± 8.7 months (range 0.5–36 months, median 12 months).…”
Section: Resultsmentioning
confidence: 94%
“…In a randomized study comparing methotrexate 0.5 mg/kg (and folic acid) with leflunomide for juvenile rheumatoid arthritis, no serious adverse events were reported in the methotrexate group, which included 47 children from week 0 to 16 and 37 children from week 16 to 48 . From week 1 to 16, nausea and/or vomiting was reported in 34% of those in the methotrexate group, headache and nasopharyngeal symptoms were each reported in 23%, increased aminotransferase levels in 9%, and alopecia in 6%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opublikowano również wiele badań retrospektywnych dotyczących skuteczności i bezpieczeństwa stosowania MTX w NChZJ [3,22,24,[35][36][37][38]. Oceniano w nich zwykle niejednorodne grupy chorych -zarówno z ChLC, jak i WZJG, a lek podawano w różnych dawkach i w różnej postaci (głównie doustnie, w średniej dawce ok. 20 mg/ tydz.).…”
Section: Wyniki Zastosowania Metotreksatu W Leczeniu Chorób Zapalnychunclassified
“…Pokreślili też konieczność wyczerpującego informowania chorego na temat dawkowania leku, zakazu prokreacji i możliwości wystąpie-nia działań niepożądanych [22]. Także u dzieci po nieskutecznym leczeniu analogami puryn stwierdzono przydatność MTX w indukowaniu i podtrzymywaniu remisji choroby oraz bezpieczeństwo stosowania [38].…”
Section: Wyniki Zastosowania Metotreksatu W Leczeniu Chorób Zapalnychunclassified